2015 IEEE International Symposium on Information Theory (ISIT) 2015
DOI: 10.1109/isit.2015.7282864
|View full text |Cite
|
Sign up to set email alerts
|

Minimax estimation of discrete distributions

Abstract: We refine the general methodology in [1] for the construction and analysis of essentially minimax estimators for a wide class of functionals of finite dimensional parameters, and elaborate on the case of discrete distributions with support size S comparable with the number of observations n. Specifically, we determine the "smooth" and "non-smooth" regimes based on the confidence set and the smoothness of the functional. In the "non-smooth" regime, we apply an unbiased estimator for a suitable polynomial approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(81 citation statements)
references
References 52 publications
0
81
0
Order By: Relevance
“…Another possible restriction that makes the problem interesting is that the entropy of p is bounded above by some given value. A similar restriction can be found in [10] in the context of discrete distribution estimation under 1 loss. In this work, we study the possibility of providing tight bounds on EU t under the restriction of some bound on the entropy.…”
Section: Introductionmentioning
confidence: 63%
“…Another possible restriction that makes the problem interesting is that the entropy of p is bounded above by some given value. A similar restriction can be found in [10] in the context of discrete distribution estimation under 1 loss. In this work, we study the possibility of providing tight bounds on EU t under the restriction of some bound on the entropy.…”
Section: Introductionmentioning
confidence: 63%
“…The reasons are twofold: the supersymbols Y i are no longer independent, and it satisfies the asymptotic equipartition property (AEP) by the Shannon-McMillan-Breiman theorem [178]. To see the role played by ergodicity, it has been shown in [179] that minimax estimation of discrete distributions with support size S under ℓ 1 loss requires n ≫ S samples, which turns out to be S D ≪ n , or equivalently, Dln0.2emnln0.2emS, in the D -tuple distribution estimation in stochastic processes. However, [180] showed that it suffices to choose the memory length Dfalse(1εfalse)ln0.2emnH for any ε > 0 in a stationary ergodic stochastic process, where H is its entropy rate, to guarantee that the empirical joint distribution of D -tuple converges to the true joint distribution under ℓ 1 loss.…”
Section: Methodsmentioning
confidence: 99%
“…samples of a random vector X = ( X 1 , X 2 , …, X d ), where XiscriptZ, false|scriptZfalse|<, we are interested in estimating the joint distribution of X . It was shown [179] that one needs to take nfalse|scriptZ|d samples to consistently estimate the joint distribution [40], which blows up quickly with growing d . Practically, it is convenient and necessary to impose some structure on the joint distribution P X to reduce the required sample complexity.…”
Section: Methodsmentioning
confidence: 99%
“…, δ S (X)) is the minimax estimator for P under squared loss [46,Example 5.4.5]. However, it is no longer minimax under other loss functions such as ℓ 1 loss, which was investigated in [47].…”
Section: Preliminariesmentioning
confidence: 99%
“…Wu and Yang [21] independently applied the best polynomial approximation idea to entropy estimation and obtained the minimax rates. However, their estimator requires the knowledge of the alphabet size S. The approximation ideas proved to be very fruitful in Acharya et al [22], Wu and Yang [23], Han, Jiao, and Weissman [24], Jiao, Han, and Weissman [25], Bu et al [26], Orlitsky, Suresh, and Wu [27], Wu and Yang [28].…”
Section: Introductionmentioning
confidence: 99%